Reveal the Condition of Students' Identity in Facing Pornography - Advis Arin Pramesti; Riska Ahmad; Netrawati Netrawati (Global Econedu, 2019)
Self-identity has an important role in student development. Failure to cultivate this quality leads to deviant behavior such as pornography. The purpose of this study was to describe the identity of students with regard to pornography. The research methods used were quantitative with a descriptive analysis approach. The population sample included 106 public vocational students in the city of Padang selected by the proportional random sampling technique. The data collection technique in this study used a questionnaire instrument with a Likert model scale. The results showed the identity of students have a 7% contribution in identity diffusion conditions, 32% identity foreclosure conditions, 48% moratorium conditions, and 13% achievement conditions. The findings of this study might be used by counselors to help students in forming their own identities especially in the face of pornography.